Capturing Salmonella SspH2 Host Targets in Virus-Like Particles - De Meyer, Margaux; Fijalkowski, Igor; Jonckheere, Veronique; De Sutter, Delphine; Eyckerman, Sven; Van Damme, Petra (Frontiers in Medicine, 2021)
In the context of host-pathogen interactions, gram-negative bacterial virulence factors, such as effectors, may be transferred from bacterial to eukaryotic host cytoplasm by multicomponent Type III protein secretion systems (T3SSs). Central to Salmonella enterica serovar Typhimurium (S. Typhimurium) pathogenesis is the secretion of over 40 effectors by two T3SSs encoded within pathogenicity islands SPI-1 and SPI-2. These effectors manipulate miscellaneous host cellular processes, such as cytoskeleton organization and immune signaling pathways, thereby permitting host colonization and bacterial dissemination. Recent research on effector biology provided mechanistic insights for some effectors. However, for many effectors, clearly defined roles and host target repertoires—further clarifying effector interconnectivity and virulence networks—are yet to be uncovered. Here we demonstrate the utility of the recently described viral-like particle trapping technology Virotrap as an effective approach to catalogue S. Typhimurium effector-host protein complexes (EH-PCs). Mass spectrometry-based Virotrap analysis of the novel E3 ubiquitin ligase SspH2 previously shown to be implicated in modulating actin dynamics and immune signaling, exposed known host interactors PFN1 and -2 besides several putative novel, interconnected host targets. Network analysis revealed an actin(-binding) cluster among the significantly enriched hits for SspH2, consistent with the known localization of the S-palmitoylated effector with actin cytoskeleton components in the host. We show that Virotrap complements the current state-of-the-art toolkit to study protein complexes and represents a valuable means to screen for effector host targets in a high-throughput manner, thereby bridging the knowledge gap between effector-host interplay and pathogenesis.